2019
DOI: 10.1111/1750-3841.14820
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of California‐Grown Blood and Cara Cara Oranges Through Consumer Testing, Descriptive Analysis, and Targeted Chemical Profiling

Abstract: The acceptability of Moro, Tarocco, Cara Cara, Shahani, Bream Tarocco, Boukhobza, and Sanguinelli oranges from both commercial and research orchards was tested with adult (n = 152) and child (n = 72) consumers. Qualitative focus groups were also conducted to understand consumer familiarity and thoughts about the fruit. Sensory descriptive and chemical analyses were carried out to identify drivers of liking. Overall, consumers preferred the lighter colored varieties consisting of Tarocco, Cara Cara, and Boukhob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“…It is also notable that attribute intensity ratings were centered at the low end of the scale, but this outcome is common in agricultural products that do not reach the attribute intensities of formulated products. For example, Simons et al (2019) reported that orange flavor intensity of different orange cultivars ranged from 3.7 to 4.8 on a 10‐point scale, whereas Swegarden et al. (2019) reported that intensities of green, pungent and sulfurous attributes in kale were 29.3, 9.5, and 15.0 points on a 100‐point scale.…”
Section: Resultsmentioning
confidence: 99%
“…It is also notable that attribute intensity ratings were centered at the low end of the scale, but this outcome is common in agricultural products that do not reach the attribute intensities of formulated products. For example, Simons et al (2019) reported that orange flavor intensity of different orange cultivars ranged from 3.7 to 4.8 on a 10‐point scale, whereas Swegarden et al. (2019) reported that intensities of green, pungent and sulfurous attributes in kale were 29.3, 9.5, and 15.0 points on a 100‐point scale.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, only a few studies in the food consumption literature have focused attention on consumer preferences for citrus fruits. Furthermore, the bulk of this literature has been mainly undertaken in the USA, e.g., [24][25][26][27][28][29][30]. Scant attention has been addressed toward consumption patterns in other countries relevant for citrus fruit production and consumption-such as Italy, the country on which the current study specifically focuses.…”
Section: Introductionmentioning
confidence: 99%
“…With the preference clustering approach, liking can be more successfully maximized for specific consumer bases by disregarding the skewed optimum that results from divergent opinions in the consumer sample. These methods and their practical application have been demonstrated in consumer acceptability studies on a variety of food products (Frost et al., 2019; Guinard, Uotani, & Schlich, 2001; Santa Cruz, Garitta, & Hough, 2003; Serrano‐Megías & López‐Nicolás, 2006; Simons et al., 2019; Thompson, Drake, Lopetcharat, & Yates, 2006). Any updated versions of the Coffee Brewing Control Chart should therefore consider this variability in coffee preferences before defining optimum or “ideal” extraction profiles.…”
Section: Discussionmentioning
confidence: 99%